Antibiofilm Activity of Epinecidin-1 and Its Variants Against Drug-Resistant Candida krusei and Candida tropicalis Isolates from Vaginal Candidiasis Patients - Sivakumar Jeyarajan; Sukumar Ranjith; Raja Veerapandian; Kalimuthusamy Natarajaseenivasan; Prahalathan Chidambaram; Anbarasu Kumarasamy (Infectious Disease Reports)
Background/Objective: Indwelling intrauterine contraceptive devices (IUDs) have surfaces that facilitate the attachment of Candida spp., creating a suitable environment for biofilm formation. Due to this, vulvovaginal candidiasis (VVC) is frequently linked to IUD usage, necessitating the prompt removal of these devices for effective treatment. In this study, we evaluated the susceptibility of antimicrobial peptides in vitro against biofilm forming, Amphotericin B (MIC50 > 2 mg L−1) resistant Candida krusei and Candida tropicalis isolated from IUD users who had signs of vaginal candidiasis (hemorrhage, pelvic pain, inflammation, itching, and vaginal discharge). Three antimicrobial peptides, namely, epinecidin-1 (epi-1) and its two variants, namely, variant-1 (Var-1) and variant-2 (Var-2), which were reported to have enhanced antibacterial activity were tested against IUD isolates (C. krusei and C. tropicalis) with pathogenic form of Candida albicans as control. Variants of epi-1, namely, Var-1 and Var-2 were created by substituting lysine in the place of histidine and alanine. Methods: The antimicrobial activity was measured using the microbroth dilution method to determine the minimum inhibitory concentration (MIC) of peptides against C. albicans, C. krusei and C. tropicalis. The MIC of each peptide was used for biofilm assay by Crystal violet staining, Scanning Electron Microscopy, and Reactive Oxygen Species (ROS) assay. To find the possible mechanism of anti-biofilm activity by the peptides, their ability to interact with Candida spp. cell membrane proteins such as Exo-β-(1,3)-Glucanase, Secreted Aspartic Proteinase (Sap) 1, and N-terminal Domain Adhesin: Als 9-2 were determined through PatchDock. Results: The MIC values of peptides: epi-1, var-1 and var-2 against C. albicans are 128 μg mL−1, 64 μg mL−1 and 32 μg mL−1, C. tropicalis are 256 μg mL−1, 64 μg mL−1, and 32 μg mL−1 and C. krusei are 128 µg mL−1, 128 µg mL−1 and 64 µg mL−1, respectively. Both the variants outperformed epi-1. Specifically for tested Candida spp., var-1 showed two- to four-fold enhancements and var-2 showed two- to eight-fold enhancements compared to epi-1. Electron microscopy confirmed that the mechanism of action involves pore formation thus inducing reactive oxygen species in Candida spp. cell membrane. Computational analysis showed that the peptides have a high tendency to interact with Candida spp. cell membrane proteins such as Exo-β-(1,3)-Glucanase, Secreted Aspartic Proteinase (Sap) 1, and N-terminal Domain Adhesin: Als 9-2, thereby preventing biofilm formation. Conclusions: The in vitro evidence supports the potential use of epi-1 and its variants to be used as an anti-biofilm agent to coat IUDs in the future for therapeutic purposes.